2015
DOI: 10.1039/c5ta02950c
|View full text |Cite
|
Sign up to set email alerts
|

Tin perovskite/fullerene planar layer photovoltaics: improving the efficiency and stability of lead-free devices

Abstract: The preparation of CsSnI3 films at room temperature with defect densities low enough for light harvesting in photovoltaic devices is reported, along with a new strategy for improving device stability and evidence that the energetics at the perovskite/fullerene interface is a key determinant of the open-circuit voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 49 publications
5
150
2
4
Order By: Relevance
“…Hatton and co-workers reported that adding an excess of tin chloride (SnCl 2 ) and tin iodide (SnI 2 ) to CsSnI 3 films improves both the stability and PCE of the corresponding solar cells, which displayed a PCE of ≈3%. [20,21] Just before the submission of this manuscript, Zhao et al reported tinbased HPSCs with a PCE of 8.12% by using mixed cation tin perovskite (FA 0.75 MA 0.25 SnI 3 ) as light harvesting layer. [22] Despite the relatively high efficiency, the resistance to moisture of FA 0.75 MA 0.25 SnI 3 -based HPSCs should be quite limited because of the hydrophilic FA + and MA + cations.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%
See 1 more Smart Citation
“…Hatton and co-workers reported that adding an excess of tin chloride (SnCl 2 ) and tin iodide (SnI 2 ) to CsSnI 3 films improves both the stability and PCE of the corresponding solar cells, which displayed a PCE of ≈3%. [20,21] Just before the submission of this manuscript, Zhao et al reported tinbased HPSCs with a PCE of 8.12% by using mixed cation tin perovskite (FA 0.75 MA 0.25 SnI 3 ) as light harvesting layer. [22] Despite the relatively high efficiency, the resistance to moisture of FA 0.75 MA 0.25 SnI 3 -based HPSCs should be quite limited because of the hydrophilic FA + and MA + cations.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%
“…[12,13] In an attempt to improve the PCE, research efforts have been directed towards optimization of the tin-perovskite film morphology, tuning the film composition, use of a reducing agent, and modification of the device structure. [14][15][16][17][18][19][20][21] The main challenges for further improving the PCE lie in preventing the easy formation of Sn vacancies due to their small formation energy and the fast oxidation of divalent Sn 2+ into more stable Sn 4+ . This causes high levels of self-p-doping in Sn-based perovskite films, with consequent severe recombination losses for charge carriers.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%
“…To date it has been used as the light harvesting semiconductor in PV devices based on mesoporous TiO 2 5,6 and planar [7][8][9] device architectures, demonstrating the potential to achieve very high short circuit current density ( J sc ) of 420 mA cm À2 under one sun illumination 6 and high device fill factor (FF). 8 The primary factor limiting the power conversion efficiency of B-g CsSnI 3 based PVs is the low open-circuit voltage (V oc ): to date the highest V oc reported is 0.55 V, 8 achieved for an inverted device architecture using phenyl-C 61 -butyric acid methylester (PCBM) as the electron transport layer (ETL), which is approximately half that attainable using the lead analogue CsPbI 3 .…”
mentioning
confidence: 99%
“…10 When using C 60 in place of PCBM the highest V oc reported is reduced to 0.36 V due to the larger electron affinity of the former. 9 The V oc in inverted perovskite PV devices depends strongly on a number of factors including the energetics at the perovskite-ETL interface 7 and the degree of crystallinity in the ETL. 11 Additionally, for PV devices using B-g CsSnI 3 as the light harvesting layer, we have shown that SnCl 2 is an effective additive for reducing the density of tin vacancy defects in the band gap and reducing the reverse saturation current, 8 both of which help to improve V oc .…”
mentioning
confidence: 99%
“…The incorporation of Sn has been reported by a study employing a structure of ITO/CuI/CsSnI 3 /C 60 /BCP/ Al [82]. The study also demonstrated the improvement in stability and performance using excess amount SnI 2 during the synthesis of CsSnI 3 .…”
Section: Lead-free Perovskite Solar Cellmentioning
confidence: 86%